Features of forming specialized glossaries (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the forming specialized glossaries. Benefits of its use in the translation work are proven. The content of the course on the basics of drawing up specialized glossaries is presented. The algorithm of forming glossaries is proposed.
Keywords: dictionary; lexicography; glossary; term; translator